The manifestations and manifestations of nature In the narrative group (The Dream and the Future) by (Lina Kilani) - Abbas Al-Sarraj, Raeeda (Journal of College of Education, 2020)
Nature  its roots  assets and manifestations constitute a major pillar of the children's literature in general and the child's story in particular, It seems that the child's story book has understood this axiom giving nature and its contents a great deal of attention in line with the level and attention of the children's group to which the child's literature is directed, The beginning of learning child to catch the pen and try to draw example we find that the river and the mountain and the tree and the sun and birds and animals are the main pillars that constitute the child's painting in the beginning of his interest in drawing, and this confirms the depth of the relationship between nature and the imagination of the child that activates and motivates in Express itself  by relying on nature and its assets. In this research we will discuss the group  "The Dream and the Future" by Lina Kilani, who notice in her reading of the nature of nature and its manifestations, is noted in a remarkable way in the story of this group. We divided the research into two paragraphs to follow nature here the first paragraph to fixed nature and its appearances  From tree, stone, mountain and other fixed elements, while we devoted the second paragraph to the moving nature such as storms, animals, birds and other manifestations and objects of natural moving, and we provided before the introduction of a theoretical talk about the nature and manifestations in general and their presence in the child literature  especially the views that have been said by some scholars in this regard, and we have analyzed elected models of Lina Kilani stories in the narrative collection mentioned having regard to diversification and comprehensive coverage as much as possible to the most important aspects and things of nature which formed an anchor narrative of the building, which is a public body of the group (the dream and the future).